المحاسبة عن الاستثمار وقياس عائده في الموارد البشرية : بالتطبيق على كلية الادارة و الاقتصاد/جامعة تكريت - صدام محمد محمود (PROSPECTIVE RESEARCHES, 2023)
The success of the institutions occasionally depends on the skill and effectiveness of employees and their satisfaction, cooperation, understanding on the key objectives for which it was. Therefore, the best investment is that to build and develop the human resource by making expenditures (investments) on them to raise their efficiency and performance of any facility. The nature of their business is keen on spending money especially in the areas of investments. Which are always seeking studying and developing a vision for a prospective investment returns. The process of identifying and measuring returns on investments in general, and measuring return on investment of human resources, in particular has its difficulties and obstacles. Therefore, the methods and approaches proposed in the measurements are various, Such as the financial (quantitative), and non-financial (descriptive), which are proposed and renewed from time to time. This research aims at identifying and measuring the value of human resources and the showing the importance and the need of its investment and the work to develop it and then measuring the expected returns of investments, to support and promote such an attempt educational institutions (universities in particular) have been chooser. Because they have a lot of persons and the fields of their investment are wide and necessary, therefore the measurement of human resources needs a method or means to measure the expected savings from these investments.